Lecciones de memoria. El recuerdo de 1971 en las protestas estudiantiles de 2011 en Colombia (2014)
This paper shows how the actualization of memory about the 1971 student protest helped, forty years later, to strengthen the unity and overcome the sectarianism of mobilizations for the right to education in Colombia. In the first place, the general features of both episodes are reconstructed, and then, the author examines the ways in which memory about what happened in 1971 worked to define a route for movement of 2011